An improved method for inducing prometaphase chromosomes in plants - Setiawan, Agus Budi; Teo, Chee How; Kikuchi, Shinji; Sassa, Hidenori; Koba, Takato (BMC, 2018)
Background: Detailed karyotyping using metaphase chromosomes in melon (Cucumis melo L.) remains a challenge because of their small chromosome sizes and poor stainability. Prometaphase chromosomes, which are two times longer and loosely condensed, provide a significantly better resolution for fluorescence in situ hybridization (FISH) than metaphase chromosomes. However, suitable method for acquiring prometaphase chromosomes in melon have been poorly investigated. Results: In this study, a modified Carnoy's solution II (MC II) [6:3:1 (v/v) ethanol: acetic acid: chloroform] was used as a pretreatment solution to obtain prometaphase chromosomes. We demonstrated that the prometaphase chromosomes obtained using the MC II method are excellent for karyotyping and FISH analysis. We also observed that a combination of MC II and the modified air dry (ADI) method provides a satisfactory meiotic pachytene chromosome preparation with reduced cytoplasmic background and clear chromatin spreads. Moreover, we demonstrated that pachytene and prometaphase chromosomes of melon and Abelia × grandiflora generate significantly better FISH images when prepared using the method described. We confirmed, for the first time, that Abelia × grandiflora has pairs of both strong and weak 45S ribosomal DNA signals on the short arms of their metaphase chromosomes. Conclusion: The MC II and ADI method are simple and effective for acquiring prometaphase and pachytene chromosomes with reduced cytoplasm background in plants. Our methods provide high-resolution FISH images that can help accelerate molecular cytogenetic research in plants.